2022
DOI: 10.1177/07410883221127998
|View full text |Cite
|
Sign up to set email alerts
|

Writing Process Feedback Based on Keystroke Logging and Comparison With Exemplars: Effects on the Quality and Process of Synthesis Texts

Abstract: This intervention study aimed to test the effect of writing process feedback. Sixty-five Grade 10 students received a personal report based on keystroke logging data, including information on several writing process aspects. Participants compared their writing process to exemplar processes of equally scoring (position-setting condition) or higher-scoring students (feed-forward condition). The effect of the feedback on writing performance and process was compared to a national baseline study. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…The educators in this study echoed previous research (Vandermeulen et al, 2023;Van Ockenburg et al, 2019), stressing the paramount importance of synthesis writing for university students, a sentiment supported by Luna et al (2022), who identified synthesis writing as fundamental for academic success. Synthesizing information from multiple sources not only meets university requirements but also nurtures critical thinking and analytical skills crucial for higher education.…”
Section: Importance Of Synthesis Writingsupporting
confidence: 75%
See 3 more Smart Citations
“…The educators in this study echoed previous research (Vandermeulen et al, 2023;Van Ockenburg et al, 2019), stressing the paramount importance of synthesis writing for university students, a sentiment supported by Luna et al (2022), who identified synthesis writing as fundamental for academic success. Synthesizing information from multiple sources not only meets university requirements but also nurtures critical thinking and analytical skills crucial for higher education.…”
Section: Importance Of Synthesis Writingsupporting
confidence: 75%
“…Acquisition of these skills is imperative in the context of higher education because it contributes to academic literacy (Castillo-Martínez & Ramírez-Montoya, 2021). However, synthesis writing does not simply involve a "reading-then-writing" strategy but demands a complex interaction of reading and writing processes (Vandermeulen et al, 2023). Based on the cognitive writing model by Flower and Hayes (1981), synthesis writing is cognitively more taxing because it adds an extra step during the planning stage, which is multiple-text comprehension.…”
Section: Importance Of Synthesis Writingmentioning
confidence: 99%
See 2 more Smart Citations
“…As these sources often present complementary (information across different sources is part of a larger whole not specified in any single source) or conflicting information, student writers are tasked with synthesizing or integrating information across different perspectives and arguments to demonstrate their writing competence or communicate their understanding. Such multiple-source based, integrated academic writing tasks have been found to represent a formidable challenge across educational levels that may require particular instructional interventions ( Mateos et al, 2018 ; Weston-Sementelli et al, 2018 ; Granado-Peinado et al, 2019 ; Du and List, 2020 ; Kiili et al, 2020 ; Marttunen and Kiili, 2022 ; Barzilai et al, 2023 ; Kullberg et al, 2023 ; Vandermeulen et al, 2023a ). As such, they can also be assumed to require considerable motivation on the part of the students, not least with respect to their confidence in their ability to successfully complete such tasks (i.e., their self-efficacy beliefs; Bandura, 1997 ).…”
Section: Introductionmentioning
confidence: 99%